HOUT-10. TREATMENT OUTCOME IN ADOLESCENTS AND YOUNG ADULTS (AYAS) WITH GLIOBLASTOMA. (11th November 2019) - An, Josiah; Chennamadhavuni, Adithya; Mott, Sarah; Garje, Rohan
Abstract: BACKGROUND: Glioblastoma is one of the most aggressive and commonly encountered brain tumors. Standard of care includes surgical resection with adjuvant or concurrent chemoradiation which is predominantly based on adult clinical trials. Our study objective was to assess whether survival differed in AYA compared to older adults. METHODS: The National Cancer Database was used to identify patients with at least surgically resected glioblastoma from 2004 to 2016. Cox regression models were utilized to estimate the effect of treatment on overall survival (OS) while accounting for immortal time bias (3-months) and clustering within facility. RESULTS: Among 51, 718 patients with glioblastoma identified, 2, 930 patients were AYA. Multivariable analysis (MVA) shows OS was significantly higher in AYA, female, non-white, high income, unilateral cancer patients with private insurance receiving treatments in high volume facilities. OS among AYA patients was significantly lower in surgery + (radiation or chemotherapy: S+(RT or CT) group compared to surgery only (S) (HR=1.33, 95% CI 1.06–1.65), but no significant survival difference between surgery + chemoradiation (S+C+RT) groups and surgery only (HR=0.97, 95% CI 0.83–1.14). Median survival is 28 months in AYA among S and S+C+RT groups whereas significantly lower survival (median OS 18 months) is seen in S+RT or CT. Non-AYA patients were at 2 times increased risk of death compared to AYA patients who received the same type of treatment. CONCLUSIONS: In conclusion, AYA population has more than twice the median OS in comparison to non-AYA patients. Worse overall survival was seen among S+RT or CT in comparison to S and S+RT+CT in AYA group. For patients needing either chemotherapy or radiation with surgery, possibly a trimodal approach might provide better survival advantage. Prospective studies are needed to further explore optimal treatment modalities in this unique population.